Ceftibuten-induced filamentation of extended spectrum beta lactamase (ESBL)-producing uropathogenic Escherichia coli alters host cell responses during an in vitro infection. (January 2015) - Demirel, Isak; Kruse, Robert; Önnberg, Anna; Persson, Katarina
Abstract: Inadequate and delayed antibiotic treatment of extended spectrum beta-lactamase (ESBL)-producing isolates have been associated with increased mortality of affected patients. The purpose of this study was to compare the host response of human renal epithelial cells and polymorphonuclear leucocyte (PMN) cells when infected by ESBL-producing uropathogenic Escherichia coli (UPEC) isolates in the presence or absence of ineffective antibiotics. The renal epithelial cell line A498 and PMN cells were stimulated with ESBL-producing UPEC isolates in the presence or absence of three different antibiotics (trimetoprim, ceftibuten and ciprofloxacin). Host cell responses were evaluated as release of cytokines (IL-6, IL-8), reactive oxygen species (ROS), ATP and endotoxins. Bacterial morphology and PMN phagocytosis were evaluated by microscopy. In the presence of ceftibuten, 2 out of 3 examined ESBL-isolates changed their morphology into a filamentous form. The presence of ceftibuten enhanced IL-6, IL-8 and ROS-production from host cells, but only from cells stimulated by the filamentous isolates. The bacterial supernatant and not the filamentous bacteria per se was responsible for the increased release of IL-6, IL-8 and ROS. Increased endotoxin and ATP levels were found in the bacterial supernatants from filamentous isolates. Apyrase decreased IL-6 secretion from A498 cells and polymyxin B abolished the increased ROS-production from PMN cells. PMN were able to inhibit the bacterial growth of some ESBL-isolates in the presence of ceftibuten. In conclusion, antibiotic-induced filamentation of ESBL-producing UPEC isolates and the associated release of ATP and endotoxins can alter the host cell response in the urinary tract. Highlights: Ineffective antibiotics induce filamentation of ESBL-producing Escherichia coli . Filamentation was associated with increased release of bacterial LPS and ATP. The released ATP induced an increased IL-6 release from renal epithelial cells. The released LPS stimulated an increased ROS-production from PMN cells.